Intelligent analysis and processing technology of big data based on clustering algorithm - Zheng, Zheng; Cao, Fukai; Gao, Song; Sharma, Amit (Informatica, 2022)
In order to study the big data intelligent analysis and processing technology based on clustering algorithm, an attribute category clustering method based on hierarchical clustering is proposed, which combines the attribute categories with similar fault type distribution, reduces the data dimension, and binarizes it. Aiming at the problem of more missing values of continuous data, a data completion method based on attribute distribution function is adopted. Then, from the perspective of the selection and estimation of project unit price in construction enterprises, this paper combs and summarizes the data mining process facing the characteristics of project cost data, and puts forward the method of analyzing and processing project cost data based on clustering algorithm. Finally, the processed data sets are subjected to bottom-up hierarchical clustering analysis, and finally the ideal analysis results can be obtained. The experimental results show that the preprocessing method based on attribute clustering proposed in this paper can effectively merge attributes, reduce the dimension after binary transformation and effectively reduce the amount of data under the condition of ensuring data information.